Comparação de métodos de raleio manual, químico e mecânico de frutos - Pavanello, Alexandre Pozzobom (2016)
The harvest of fruits of high quality provides increased market value for the fruit grower. A effective fruit thinning is of the most important steps to provide good commercialization. The increased occurrence of hail storms during the growing period resulted in the installation of protective hail nets. This study aimed to evaluate the effects of chemical and mechanical thinning in plums and hand, chemical and mechanical thinning in apples for different hail nets.. For thinning in plums, mechanical thinning was more efficient when compared to chemical thinning. The mechanical thinning treatment reduced fruit set, number of fruit per tree and yield, however it increased fruit size, fruit weight and promoted higher vegetative growth, an important factor to avoid alternating production every year. For apple thinning, mechanical thinning was an effective fruit thinner. It was observed that some treatments like CT-BA required around 300 hours or more per hectare of hand thinning to achieve a satisfactory thinning efficacy. The black hail nets showed a reduction in red colour in apples. The thinning efficacy value (TEV) for hand thinning was 93%, for mechanical thinning was 74%, for chemical thinning with Metamitron was 62% and for chemical thinning with Benzyladenine was 54%.